Diet-wide association study of 92 foods and nutrients and lung cancer risk in the European Prospective Investigation into Cancer and Nutrition study and the Netherlands Cohort Study - Heath,AK; Muller,DC; van,den Brandt PA; Critselis,E; Gunter,M; Vineis,P; Weiderpass,E; Boeing,H; Ferrari,P; Merritt,MA; Rostgaard-Hansen,AL; Tjonneland,A; et al. (International Journal of Cancer, 2022)
Diet-wide association study of 92 foods and nutrients and lung cancer risk in the European Prospective Investigation into Cancer and Nutrition study and the Netherlands Cohort Study